2022
DOI: 10.3389/fpls.2022.860455
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Co-expression Network Analysis Reveal the Importance of Hub Proteins and Metabolic Pathways in Nicotine Synthesis and Accumulation in Tobacco (Nicotiana tabacum L.)

Abstract: Nicotine is a unique alkaloid present in tobacco that is widely used in cigarettes and in the agricultural, chemical, and pharmaceutical industries. However, the research on nicotine is mostly limited to its synthesis pathways, and only a few studies have explored the effects of other metabolic pathways on nicotine precursors. Regulating the nicotine content in tobacco can greatly promoting the application of nicotine in other fields. In this study, we performed global data-independent acquisition proteomics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…This gene was rapidly regulated by light and through additional studies, such as overexpression in pear peel and calli and Y2H, confirming its role in anthocyanin biosynthesis and also clarifying its mechanism of action [112]. Nicotine biosynthesis in tobacco was also investigated with WGCNA using different varieties with high and low metabolite content [105]. In this work, coexpressed modules were correlated with nicotine accumulation as an external trait, and genes associated to this module were related to metabolism of nicotine precursors such as Arg, Orn, Asp, Pro and GSH.…”
Section: Applications In Plant Biologymentioning
confidence: 80%
See 1 more Smart Citation
“…This gene was rapidly regulated by light and through additional studies, such as overexpression in pear peel and calli and Y2H, confirming its role in anthocyanin biosynthesis and also clarifying its mechanism of action [112]. Nicotine biosynthesis in tobacco was also investigated with WGCNA using different varieties with high and low metabolite content [105]. In this work, coexpressed modules were correlated with nicotine accumulation as an external trait, and genes associated to this module were related to metabolism of nicotine precursors such as Arg, Orn, Asp, Pro and GSH.…”
Section: Applications In Plant Biologymentioning
confidence: 80%
“…The most straightforward application of co-expression network analysis is the study of metabolic pathways and their regulation [104][105][106][107], including plant stress responses [108][109][110] and, more importantly, the identification of potential candidates for the biotechnological improvement of crops [51]. This is of special relevance, as it makes it possible to directly transfer all knowledge gained in model species over the years to species of agronomic interest, such as soybean [108].…”
Section: Applications In Plant Biologymentioning
confidence: 99%
“…Currently, seven distinct modules possessing candidate proteins linked to V. dahliae resistance have been identified (Figure 3b). Previous studies have also highlighted the significance of coexpression network analysis in identifying hub genes/proteins (Mo et al, 2022; Proost & Mutwil, 2017). RT‐qPCR was used to study the expression dynamics of identified candidates as described previously (Ju et al, 2023; Wu et al, 2022; Xiong et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is the major (0.6~3.0% of the dry weight) alkaloid present in Nicotiana spp. [ 44 , 45 ]. Nicotine does not initiate cancer but can affect cancer development through activation and binding with the acetylcholine receptors to synthase tobacco-specific N-nitrosamines or inhibition of immune response by affecting dendritic cells [ 46 ].…”
Section: Anti-cancer Alkaloids Present In Nicotianamentioning
confidence: 99%